PERANAN REMAJA DALAM KEAKTIFAN PELAYANAN DAN PERKAMBANGAN GEREJA - Megawati manullang (JURNAL PIONIR, 2022)
Abstract Adolescence is a very productive period to be nurtured and guided in ministry. If youth are nurtured to the maximum, they will have a positive influence on others and also on the growth of the church because youth will become the next generation who will continue the duties and responsibilities of the Church as witnesses of Christ in the midst of a world full of challenges. A world full of challenges, needs to be lit up with the presence of God-fearing youth. This starts from the formation of youth in ministry in the church.Keywords: Youth, Church                                                           AbstrakMasa remaja adalah masa yang sangat produktif untuk dibina dan di bimbing dalam pelayanan.  Apabila remaja dibina dengan maksimal, mereka akan membawa pengaruh positif  bagi sesama dan juga terhadap pertumbuhan gereja karena remaja akan menjadi generasi penerus yang akan melanjutkan tugas dan tanggungjawab  Gereja sebagai saksi  Kristus di tengah-tengah dunia yang penuh dengan tantangan ini. Dunia yang penuh dengan tantangan, perlu di terangi dengan kehadiran para remaja yang takut akan Tuhan. Ini dimulai dari pembinaan remaja dalam pelayanan di gereja. Kata kunci: Remaja, Gereja.